Cyber Security of the Economy and Public Finances: Historiography and Post-War Trajectory of Development - Petrukha Nina M.; Petrukha Serhii V.; Zhmaiev Anatolii Yu.; Synkevych Maksym E. (Bìznes Inform)
The article examines the evolution of the cyber security paradigm in the context of the ontogenesis of the economy and public finances with an emphasis on the triggers of pre-war and war-oriented institutional memory and challenges in the post-war reconstruction of Ukraine. The scientific novelty consists in a comprehensive study of historiographical processes in cyber security and their impact on dynamic shifts in the economy and public finances, considering endo- and exogenous cyber challenges and opportunities for digital transformation and all-encompassing digitalization formed by the new economic reality. It was found that the emergence and strengthening of the role of artificial intelligence allows for a closer level of correlation between trends in the development of the economy and public finances by adding new data to predictive models, bringing them to the level of big data, identifying threats and risks in them for the development of adaptive anti-crisis-colored regulatory behavioral models for the State regulators, including in terms of creating formal and informal institutional rules for countering cyber threats. On the basis of this, practical recommendations on increasing the efficiency and productivity of the level of cyber security were formed, which correspond to the existing strategic document in this area – the Cyber Security Strategy of Ukraine, which stitches together niche strategic documents (such as the Plan for the Ukraine Facility, the Strategy for the Reform of the State Finance Management System for 2022–2025) by a single cyber defense system.